Double-phase titanium-based high-entropy hydrogen storage alloy with low-temperature efficient hydrogen storage performance and preparation and application of double-phase titanium-based high-entropy hydrogen storage alloy

By adopting a biphasic titanium-based high-entropy hydrogen storage alloy, the two phase synergistic effect of coexisting two different sets of C14 Laves phase structures is solved, and the existing high-entropy hydrogen storage alloys are poorly stored in low temperature conditions is achieved, achieving efficient low-temperature hydrogen absorption and discharge performance and good cycle stability.

CN119640121APending Publication Date: 2025-03-18NORTH CHINA POWER ENG
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411598823.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing AB2 high-entropy hydrogen storage alloy with Laves-type structure is difficult to achieve high hydrogen storage capacity, cycle stability and excellent hydrogen absorption and discharge performance under mild conditions, especially in the low-temperature dehydrogenation behavior, which requires new phase change pathways.

Method used

A biphasic titanium-based high-entropy hydrogen storage alloy is used, and its chemical expression is TiaZrbCrcMndNieVfFeg. By smelting raw materials and forming two different hexagonal C14-type Laves phase structures, the coexistence of C14-I phase and C14-II phase produces a biphasic synergistic effect, reducing the energy barrier for hydrogen absorption and release reaction.

Benefits of technology

The saturation capacity of 1.83 wt% H2 can be quickly reached at 0°C without activation treatment, and desorbed 1.77 wt% H2 at the starting dehydrogenation temperature of 20°C, with a dehydrogenation rate greater than 96.7%, and showed good hydrogen absorption and release cycle stability. After 20 cycles, the capacity retention rates of hydrogen absorption and release can reach 97.8% and 97.0% respectively.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640121A_ABST
    Figure CN119640121A_ABST
Patent Text Reader

Abstract

The invention discloses a biphase titanium-based high-entropy hydrogen storage alloy with low-temperature efficient hydrogen storage performance, a preparation method of the biphase titanium-based high-entropy hydrogen storage alloy and application of the biphase titanium-based high-entropy hydrogen storage alloy in hydrogen absorption and desorption. The chemical expression of the biphase titanium-based high-entropy hydrogen storage alloy with the low-temperature efficient hydrogen storage performance is TiaZrbCrcMndNieVfFeg, a, b, c, d, e, f and g all represent atomic ratios, a, b, c, d and e are respectively and independently 0.95 to 1.05, f is 0.77 to 0.85, g is 0.18 to 0.20, and the sum of f and g is 0.95 to 1.05. The preparation method comprises the following steps: (1) mixing Ti, Zr, Cr, Mn, Ni and ferrovanadium alloy raw materials according to a chemical expression; and (2) smelting the raw materials mixed in the step (1), and cooling and solidifying after smelting to obtain the biphase titanium-based high-entropy hydrogen storage alloy with low-temperature efficient hydrogen storage performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of hydrogen storage materials, and in particular to a dual-phase titanium-based high-entropy hydrogen storage alloy with low-temperature and high-efficiency hydrogen storage performance, and a preparation method and application thereof. Background Art

[0002] With the rapid development of social economy, human demand for energy is growing, and traditional fossil fuels are facing depletion. At the same time, the over-exploitation and use of traditional fossil fuels have caused serious environmental pollution. Therefore, the development of clean, pollution-free and efficient renewable energy has become an urgent task today.

[0003] Hydrogen is an ideal energy carrier to alleviate the pollution and resource crisis caused by the combustion of fossil fuels. However, achieving effective storage and utilization of hydrogen is the top priority for the development of hydrogen energy. Compared with traditional high-pressure gaseous and liquid hydrogen storage methods, solid-state hydrogen storage technology has higher safety, hydrogen storage capacity and lower cost.

[0004] In recent decades, various types of hydrogen storage alloys have been developed and studied for practical applications. One major research direction involves increasing the number of elements in the alloy to enhance the comprehensive hydrogen storage properties.

[0005] High entropy alloys (HEAs) are alloys composed of five or more alloying elements, with the concentration of each alloying element ranging from 5 to 35 at%.

[0006] Compared with AB and AB5 materials, AB2 HEAs with Laves structure usually have higher cycle stability and excellent kinetic performance. For example, Kunce et al. studied Ti-Zr-V-Cr-Fe-Ni HEA with C14 Laves phase. After thermal activation at 500°C for 2 hours, its hydrogen storage capacity can be close to 1.80wt% under hydrogenation conditions of 50°C and 10MPa, but the hydrogenation pressure of the sample is too high (I.Kunce, M.Polanski, J.Bystrzycki, Structure and hydrogen storage properties of a high entropy ZrTiVCrFeNi alloy synthesized using LaserEngineered Net Shaping(LENS), Int.J.Hydrogen Energy 38(27)(2013)12180-12189.). Edalati et al. set the valence electron concentration (VEC) to 6.4 and used AB2-type element composition to prepare C14 Laves-type TiZrCrMnFeNi HEA for the first time. The alloy achieved reversible hydrogen absorption and desorption, with an equilibrium pressure of about 1 MPa and a saturation capacity of 1.70wt%. Its reversible hydrogen absorption and desorption capacity needs to be further improved (P.Edalati, R.Floriano, A.Mohammadi, YTLi, G.Zepon, HWLi, K.Edalati, Reversible room temperature hydrogen storage inhigh-entropy alloy TiZrCrMnFeNi, Scr.Mater.178(2020)387-390.).

[0007] At present, it is still difficult for AB2-type high-entropy hydrogen storage alloys with a Laves-type structure to simultaneously achieve high hydrogen storage capacity, cyclic stability and excellent hydrogen absorption and desorption performance under mild conditions. In particular, for low-temperature dehydrogenation behavior, it is necessary to establish a new phase transition pathway in the hydrogen absorption and desorption process. Summary of the invention

[0008] In view of the above-mentioned technical problems and the deficiencies in the art, the present invention provides a dual-phase titanium-based high entropy hydrogen storage alloy with low-temperature and high-efficiency hydrogen storage performance, and a preparation method and application thereof.

[0009] The specific technical solutions are as follows:

[0010] [1] A dual-phase titanium-based high entropy hydrogen storage alloy with low-temperature and high-efficiency hydrogen storage performance, the chemical formula is Ti a Zr b Crc Mn d Ni e V f Fe g , wherein a, b, c, d, e, f, and g all represent atomic ratios, and a, b, c, d, and e are independently 0.95 to 1.05, f is 0.77 to 0.85, g is 0.18 to 0.20, and the sum of f and g is 0.95 to 1.05.

[0011] In the chemical expression, V f Fe g It can be derived from ferrovanadium alloy, in which, taking the total mass of vanadium and iron as 100%, the mass percentage of vanadium can be 78%-82%, further can be 80%, the mass percentage of iron can be 18%-22%, further can be 20%, and Ti, Zr, Cr, Mn, and Ni can be derived from their respective metal elements.

[0012] In some embodiments, in the chemical expression, a, b, c, d, and e can be independently 0.98 to 1.03 (eg, 1.01, etc.), and are preferably all 1.

[0013] In some embodiments, in the chemical expression, f may be 0.78 to 0.84.

[0014] In some embodiments, in the chemical expression, the sum of f and g may be 0.96 to 1.04.

[0015] In the chemical expression, the sum of f and g is preferably 1.

[0016] In a preferred example, in the chemical expression, a, b, c, d, and e are all 1, f is 0.81, and g is 0.19.

[0017] The dual-phase titanium-based high entropy hydrogen storage alloy with low-temperature and high-efficiency hydrogen storage performance has two groups of different hexagonal C14-type Laves phase structures, and the two groups of different hexagonal C14-type Laves phase structures are C14-I phase and C14-II phase respectively;

[0018] The structural refinement data of the C14-I phase and the C14-II phase are as follows:

[0019] Unit cell parameter information:

[0020]

[0021] Interplanar spacing information:

[0022]

[0023] The coexistence of the above two groups of different C14-type Laves phase structures can produce a two-phase synergistic effect, which reduces the energy barrier of the hydrogen absorption and desorption reactions of the two-phase titanium-based high entropy hydrogen storage alloy with low-temperature and high-efficiency hydrogen storage performance, promotes the hydrogen absorption and desorption process, and makes the two-phase titanium-based high entropy hydrogen storage alloy with low-temperature and high-efficiency hydrogen storage performance have excellent low-temperature hydrogen absorption and desorption performance.

[0024] The dual-phase titanium-based high entropy hydrogen storage alloy with low-temperature and efficient hydrogen storage performance can quickly reach a saturation capacity of 1.83wt% H2 at 0°C without any activation treatment, and then desorb 1.77wt% H2 at an initial dehydrogenation temperature of 20°C, with a dehydrogenation rate of greater than 96.7%.

[0025] The dual-phase titanium-based high entropy hydrogen storage alloy with low-temperature and high-efficiency hydrogen storage performance also has good hydrogen absorption and desorption cycle stability. After 20 cycles, the capacity retention rates of hydrogen absorption and desorption can reach 97.8% and 97.0%, respectively.

[0026] [2] A method for preparing a dual-phase titanium-based high entropy hydrogen storage alloy having low-temperature and high-efficiency hydrogen storage performance according to [1], comprising the steps of:

[0027] (1) mixing Ti, Zr, Cr, Mn, Ni and ferrovanadium alloy raw materials according to the chemical expression;

[0028] (2) The raw materials mixed in step (1) are smelted, and after smelting, they are cooled and solidified to obtain the dual-phase titanium-based high entropy hydrogen storage alloy with low-temperature and high-efficiency hydrogen storage performance.

[0029] In step (1), in the vanadium-iron alloy, based on the total mass of vanadium and iron as 100%, the mass percentage of vanadium can be 78% to 82%, further can be 80%, and the mass percentage of iron can be 18% to 22%, further can be 20%.

[0030] In step (2), the raw materials mixed in step (1) can be placed in a magnetic suspension induction melting furnace for melting.

[0031] In step (2), the smelting is preferably carried out under the protection of an inert gas. The inert gas refers to a gas that does not participate in the reaction. Preferably, the inert gas is argon. In some embodiments, the pressure of the inert gas may be 1.2 to 1.4 bar.

[0032] In step (2), the melting-cooling and solidification process can be performed multiple times (3 to 5 times) to ensure that the composition of the alloy ingot is uniform.

[0033] [3] Application of the dual-phase titanium-based high entropy hydrogen storage alloy with low-temperature and high-efficiency hydrogen storage performance described in [1] in hydrogen absorption and desorption.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] 1) The dual-phase titanium-based high entropy hydrogen storage alloy with low-temperature and efficient hydrogen storage performance of the present invention is composed of two similar but different C14 Laves phases, which are respectively recorded as C14-Ⅰ and C14-Ⅱ phases. The dual-phase titanium-based high entropy hydrogen storage alloy with low-temperature and efficient hydrogen storage performance of the present invention can quickly reach a saturated capacity of 1.83wt% H2 at 0°C without any activation treatment, and then desorb 1.77wt% H2 at an initial dehydrogenation temperature of 20°C. The dual-phase titanium-based high entropy hydrogen storage alloy with low-temperature and efficient hydrogen storage performance of the present invention shows good hydrogen absorption and desorption cycle stability. After 20 cycles, the capacity retention rates of hydrogen absorption and desorption can reach 97.8% and 97.0%, respectively.

[0036] 2) The dual-phase titanium-based high entropy hydrogen storage alloy with low-temperature and efficient hydrogen storage performance of the present invention has a special dual-phase structure. The dual-phase structure leads to the crossing of the hydrogen binding energy band gap. The dual-phase synergistic effect produced by the coexistence of the two phases reduces the energy barrier of the hydrogen absorption and desorption reactions, thereby improving the hydrogen absorption and desorption performance of the material. Therefore, the dual-phase titanium-based high entropy hydrogen storage alloy with low-temperature and efficient hydrogen storage performance of the present invention can realize rapid hydrogen absorption and desorption at low temperatures.

[0037] 3) The method of the present invention has simple steps and high safety. The two C14 Laves phases of the dual-phase titanium-based high entropy hydrogen storage alloy with low-temperature and high-efficiency hydrogen storage performance produce a dual-phase synergistic effect, which improves the hydrogen absorption and desorption performance of the material and provides a new way for the construction of hydrogen storage alloys in the future. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 X-ray diffraction (XRD) patterns and Rietveld refinement results of the high entropy hydrogen storage alloy ingot prepared in Example 1 in the hydrogenated state (a) and the dehydrogenated state (b);

[0039] Figure 2 The selected area electron diffraction (SAED) spectrum of the high entropy hydrogen storage alloy prepared in Example 1 and the high resolution transmission electron microscopy (HR-TEM) photos of the C14-Ⅰ and C14-Ⅱ phases;

[0040] Figure 3 The pressure-composition-temperature (PCT) curves of the high entropy hydrogen storage alloy prepared in Example 1 at different temperatures after activation;

[0041] Figure 4 is an activation curve diagram of the high entropy hydrogen storage alloy prepared in Example 1;

[0042] Figure 5 The hydrogen absorption kinetics curve of the high entropy hydrogen storage alloy prepared in Example 1 at different temperatures and 3MPa hydrogen pressure;

[0043] Figure 6 The dehydrogenation kinetics curve of the high entropy hydrogen storage alloy prepared in Example 1 at different temperatures;

[0044] Figure 7 The hydrogen absorption and desorption curve diagram of the cycle performance of the high entropy hydrogen storage alloy prepared in Example 1;

[0045] Figure 8 Ti prepared in Comparative Example 1 and Comparative Example 2 0.5 Zr 1.5 System and Ti 1.5 Zr 0.5 XRD patterns and Rietveld refinement analysis of samples of the alloy in cast and hydrogenated state;

[0046] Fig. 9 Calculation results related to the binding energy of the high entropy hydrogen storage alloy prepared in Example 1, (a) is the binding energy of the related separated C14 Laves phases (C14-Ⅰ and C14-Ⅱ) and the symbiotic C14 Laves phases (C14-Ⅰ / Ⅱ) (the hydrogenation order is from top to bottom, and the dehydrogenation order is from bottom to top), and (b) is a schematic diagram of the energy barrier of the two-phase synergistic effect during hydrogen absorption and desorption. DETAILED DESCRIPTION

[0047] The present invention will be further described below in conjunction with the accompanying drawings and specific examples. It should be understood that these examples are only intended to illustrate the present invention and are not intended to limit the scope of the present invention. The operating methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.

[0048] Example 1

[0049] In terms of atomic ratio, the chemical composition of the alloy is expressed as TiZrCrMnNiV 0.81 Fe 0.19 According to the chemical formula of the above alloy, the addition amount of Ti, Zr, Cr, Mn, Ni and ferrovanadium alloy raw materials is calculated. In addition, additional Mn is added to make up for the Mn loss during the melting process. Each melting loses about 0.5% of the total mass of Mn. Among them, the purity of the single raw materials of Ti, Zr, Cr, Mn and Ni used is more than 99%, and the ferrovanadium alloy is composed of 80wt% V and 20wt% Fe. The weighed raw materials are placed in a water-cooled copper crucible of a magnetic levitation induction melting furnace. After evacuating the air to a vacuum degree of <0.001bar, they are melted under the protection of an argon atmosphere of 1.2bar. In order to make the composition uniform, it is necessary to turn over and repeat the melting five times to obtain a high entropy hydrogen storage alloy ingot.

[0050] In order to characterize the phase structure of the high entropy hydrogen storage alloy ingot of this embodiment, XRD test was carried out on the high entropy hydrogen storage alloy ingot. The XRD spectra and Rietveld refinement results of the alloy in the hydrogenated state (3MPa hydrogen saturation) and the dehydrogenated state (dynamic vacuum at 200°C for 1 hour) are shown in Figure 2. Figure 1 As shown, it can be found that the XRD diffraction peak of the high entropy hydrogen storage alloy shows obvious broadening, indicating that the alloy is not only composed of a single C14 phase. The refinement results show that the high entropy hydrogen storage alloy has two different groups of hexagonal C14-type Laves phase structures, which can be recorded as C14-I phase and C14-II phase respectively. The structural refinement data of the C14-I phase and the C14-II phase are as follows:

[0051] Unit cell parameter information:

[0052]

[0053] Interplanar spacing information:

[0054]

[0055] Furthermore, TEM test was carried out on the high entropy hydrogen storage alloy ingot, and the test results are as follows: Figure 2 As shown, selected area electron diffraction (SAED, Figure 2 (a) shows two groups of diffraction spots, which correspond to two hexagonal C14 Laves-type structures and their different crystal planes. Through fast Fourier transform (FFT) and inverse fast Fourier transform (IFFT) analysis, it can be determined that Figure 2 (b) Figure 2 The interplanar spacing in (c) is 0.247 nm and 0.208 nm, corresponding to the (110) plane of the C14-Ⅰ phase and the (201) plane of the C14-Ⅱ phase, respectively.

[0056] In order to test the hydrogen absorption and desorption properties of the alloy, the alloy was first activated. The alloy ingot was crushed into small particles in a glove box, and 1.0g of sample powder was weighed and placed in a stainless steel reactor. Dynamic vacuum was applied at room temperature for 15 minutes to remove impurity gases adsorbed on the surface of the sample. Subsequently, hydrogenation treatment was carried out at a pressure of 3MPa for 30 minutes; then dynamic vacuum was applied at 200°C for 1 hour to achieve dehydrogenation. The whole process was repeated 3 times to ensure that the alloy sample was fully activated. The pressure-composition-temperature (PCT) curves of the activated alloy at different temperatures were then tested, such as Figure 3 As shown, the platform area of ​​the PCT curve is more inclined and the equilibrium pressure hysteresis is smaller.

[0057] In addition, under a constant hydrogen pressure of 3 MPa, the test recorded three activation curves of the high entropy hydrogen storage alloy and the hydrogenation kinetics curves at different temperatures (0, 20, 40 and 60 ° C), such as Figure 4 , Figure 5 As shown in the figure, the sample exhibits excellent low-temperature hydrogenation performance, and can quickly reach a saturated capacity of 1.83wt% H2 at 0°C without any activation treatment. The high entropy hydrogen storage alloy of this embodiment can achieve the best effect without activation treatment within the commonly used operating temperature range. In order to evaluate the dehydrogenation performance of the sample, isothermal dehydrogenation kinetic tests (100, 150, 200 and 300°C) were carried out. Figure 6 As shown in the figure, at four different temperatures, the high entropy hydrogen storage alloy can complete 99% of the dehydrogenation reaction progress within 3 minutes, and at 300°C, it can complete 97.8% of the dehydrogenation reaction progress within 30 seconds. Finally, the cyclic stability of the alloy was tested. The process included hydrogenation at room temperature for 15 minutes (initial hydrogen pressure of hydrogenation was 3MPa), isothermal dehydrogenation at 200°C for 5 minutes, and then dynamic vacuuming at 200°C for 1 hour. The cyclic performance of the alloy is shown in the figure. Figure 7 As shown, after 20 cycles, the capacity retention rates of hydrogen absorption and desorption were 97.8% and 97.0%, respectively, showing good hydrogen absorption and desorption cycle stability.

[0058] Comparative Example 1

[0059] In terms of atomic ratio, the chemical composition of the alloy is expressed as Ti 0.5 Zr 1.5 CrMnNiV 0.81 Fe 0.19 According to the chemical expression of the above alloy, the addition amount of Ti, Zr, Cr, Mn, Ni and ferrovanadium alloy raw materials is calculated. Extra Mn is added to make up for the Mn loss in the melting process. Each melting loses about 0.5% of the total mass of Mn. Among them, the purity of the single raw materials of Ti, Zr, Cr, Mn and Ni used is more than 99%, and the ferrovanadium alloy is composed of 80wt% V and 20wt% Fe. The weighed raw materials are placed in a water-cooled copper crucible of a magnetic levitation induction melting furnace. After evacuating the air to a vacuum degree of <0.001bar, they are melted under the protection of an argon atmosphere of 1.2bar. The melting time is 60 seconds. In order to make the composition uniform, it is necessary to turn over and repeat the melting five times to obtain Ti. 0.5 Zr 1.5 Alloy ingot. 0.5 Zr 1.5 The XRD patterns and Rietveld refinement results of the alloy in the cast and hydrogenated state are shown in Figure 8 (a) Figure 8 (c) Figure 8 (d) 0.5 Zr1.5 The alloy samples show a single C14 Laves phase structure in both the cast and hydrogenated states.

[0060] Comparative Example 2

[0061] In terms of atomic ratio, the chemical composition of the alloy is expressed as Ti 1.5 Zr 0.5 CrMnNiV 0.81 Fe 0.19 According to the chemical expression of the above alloy, the addition amount of Ti, Zr, Cr, Mn, Ni and ferrovanadium alloy raw materials is calculated. Extra Mn is added to make up for the Mn loss in the melting process. Each melting loses about 0.5% of the total mass of Mn. Among them, the purity of the single raw materials of Ti, Zr, Cr, Mn and Ni used is more than 99%, and the ferrovanadium alloy is composed of 80wt% V and 20wt% Fe. The weighed raw materials are placed in a water-cooled copper crucible of a magnetic levitation induction melting furnace. After evacuating the air to a vacuum degree of <0.001bar, they are melted under the protection of an argon atmosphere of 1.2bar. The melting time is 60 seconds. In order to make the composition uniform, it is necessary to turn over and repeat the melting five times to obtain Ti. 1.5 Zr 0.5 Alloy ingot. 1.5 Zr 0.5 The XRD patterns and Rietveld refinement results of the alloy in the cast and hydrogenated state are shown in Figure 8 (b) Figure 8 (e) Figure 8 (f) 1.5 Zr 0.5 The alloy samples show a single C14 Laves phase structure in both the cast and hydrogenated states.

[0062] The dual-phase titanium-based high entropy hydrogen storage alloy with low-temperature and high-efficiency hydrogen storage performance of the present invention has two different C14-type Laves phase structures. This dual-phase structure leads to the crossing of hydrogen binding energy band gaps. Taking the high entropy hydrogen storage alloy prepared in Example 1 as an example, Fig. 9 (a) The calculation results show that there are two large gaps in the binding energy of C14-Ⅰ / Ⅱ, while the binding energy at other positions is relatively concentrated. These two gaps correspond to the two inflection points on the PCT curve, marking the boundaries of the α phase, α+β phase, and β phase regions. The binding energy band gap crossing phenomenon in the dual-phase structure indicates that compared with a single C14 phase, the structure of two C14 phases can reduce the energy barrier of hydrogen absorption and desorption reactions, thereby promoting the occurrence of hydrogen absorption and desorption reactions in a dual-phase synergistic manner, as shown in Figure 2. Fig. 9 In summary, the dual-phase titanium-based high entropy hydrogen storage alloy with low-temperature and high-efficiency hydrogen storage performance of the present invention has a unique dual-phase structure, and the dual-phase structure greatly improves the hydrogen absorption and desorption performance of the material.

[0063] In addition, it should be understood that after reading the above description of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.

Claims

1. A dual-phase titanium-based high entropy hydrogen storage alloy with low-temperature and high-efficiency hydrogen storage performance, characterized in that: The chemical formula is Ti a Zr b Cr c Mn d Ni e V f Fe g , wherein a, b, c, d, e, f, and g all represent atomic ratios, and a, b, c, d, and e are independently 0.95 to 1.05, f is 0.77 to 0.85, g is 0.18 to 0.20, and the sum of f and g is 0.95 to 1.

05.

2. The dual-phase titanium-based high entropy hydrogen storage alloy with low-temperature and high-efficiency hydrogen storage performance according to claim 1, characterized in that: a, b, c, d, and e are each independently 0.98 to 1.03, and preferably all 1.

3. The dual-phase titanium-based high entropy hydrogen storage alloy with low-temperature and high-efficiency hydrogen storage performance according to claim 1, characterized in that: f is 0.78 to 0.84; the sum of f and g is 0.96 to 1.04, preferably 1.

4. The dual-phase titanium-based high entropy hydrogen storage alloy with low-temperature and high-efficiency hydrogen storage performance according to claim 1, characterized in that: a, b, c, d, and e are all 1, f is 0.81, and g is 0.

19.

5. The dual-phase titanium-based high entropy hydrogen storage alloy with low-temperature and high-efficiency hydrogen storage performance according to claim 1, characterized in that: The dual-phase titanium-based high entropy hydrogen storage alloy with low-temperature and high-efficiency hydrogen storage performance has two groups of different hexagonal C14-type Laves phase structures, and the two groups of different hexagonal C14-type Laves phase structures are C14-I phase and C14-II phase respectively; The structural refinement data of the C14-I phase and the C14-II phase are as follows: Unit cell parameter information: Interplanar spacing information:

6. The method for preparing a dual-phase titanium-based high entropy hydrogen storage alloy with low-temperature and high-efficiency hydrogen storage performance according to any one of claims 1 to 5, characterized in that: Includes steps: (1) mixing Ti, Zr, Cr, Mn, Ni and ferrovanadium alloy raw materials according to the chemical expression; (2) The raw materials mixed in step (1) are smelted, and after smelting, they are cooled and solidified to obtain the dual-phase titanium-based high entropy hydrogen storage alloy with low-temperature and high-efficiency hydrogen storage performance.

7. The preparation method according to claim 6, characterized in that: In step (1), in the vanadium-iron alloy, based on the total mass of vanadium and iron as 100%, the mass percentage of vanadium is 78% to 82%, further 80%, and the mass percentage of iron is 18% to 22%, further 20%.

8. The preparation method according to claim 6, characterized in that: In step (2): The raw materials mixed in step (1) are placed in a magnetic suspension induction melting furnace for melting The smelting is carried out under the protection of inert gas; The inert gas is argon; The pressure of the inert gas is 1.2-1.4 bar.

9. The preparation method according to claim 3, characterized in that: In step (2): Multiple melting-cooling and solidification processes are carried out to ensure uniform alloy composition.

10. Use of the dual-phase titanium-based high entropy hydrogen storage alloy with low-temperature and high-efficiency hydrogen storage performance according to any one of claims 1 to 5 in hydrogen absorption and desorption.

Citation Information

Cited By

  • TiCrNbV high-entropy hydrogen storage alloy with BCC structure and preparation method of TiCrNbV high-entropy hydrogen storage alloy

    CN120796812A